2011
DOI: 10.1007/s12032-011-0134-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-148a is silenced by hypermethylation and interacts with DNA methyltransferase 1 in gastric cancer

Abstract: Studies have shown that microRNA-148a (miR-148a) was proved to be silenced while DNA methyltransferase 1 (DNMT1) was over-expressed in gastric cancer. But the mechanism of aberrant expression of miR-148a and DNMT1 and their relationships in gastric cancer are still unknown. The aims of this study were to investigate the expression profile of miR-148a and DNMT1 and reveal whether they have any relationships. We used reverse-transcriptase quantitative real-time PCR, methylation-specific PCR and Western blot to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
79
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 30 publications
10
79
0
Order By: Relevance
“…This suggests that miR-148a may not directly target RUNX3. Previous studies have already confirmed that miR-148a could modulate DNMT1 and DNMT3B protein expression (Braconi et al, 2010;Duursma et al, 2008;Pan et al, 2010;Zhu et al, 2012). Therefore, our results show that overexpression of miR148a in gastric cancer cells might upregulate RUNX3 expression through the modulation of DNMTs.…”
Section: Overexpression Of Mir-148a Downregulated Runx3 Gene Expressionsupporting
confidence: 79%
See 4 more Smart Citations
“…This suggests that miR-148a may not directly target RUNX3. Previous studies have already confirmed that miR-148a could modulate DNMT1 and DNMT3B protein expression (Braconi et al, 2010;Duursma et al, 2008;Pan et al, 2010;Zhu et al, 2012). Therefore, our results show that overexpression of miR148a in gastric cancer cells might upregulate RUNX3 expression through the modulation of DNMTs.…”
Section: Overexpression Of Mir-148a Downregulated Runx3 Gene Expressionsupporting
confidence: 79%
“…In those studies we found that miR-148a was significantly downregulated in gastric cancer tissues (Zhu et al, 2012). Interestingly, in the present study an obvious correlation was observed between the expression of miR-148a and RUNX3 mRNA in the 38 pairs of tissue samples (r = 0.581, P < 0.001, Fig.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations